Ceramic Embedding as Packaging Solution for Future Power Electronic Applications - Bach, Hoang Linh; Endres, Tobias; Dirksen, Daniel; Zischler, Sigrid; Bayer, Christoph Friedrich; Schletz, Andreas; März, Martin (2018 IPEC International Power Electronics Conference (ECCE Asia), 2018)
This paper proposes a novel packaging concept for power electronic applications on basis of embedding power devices in ceramic circuit carriers, such as direct bonded copper (DBC) substrates. The semiconductor devices are assembled into laser structured DBC substrates and then sealed with a copper cover afterwards. This proposed method is an alternative solution to printed circuit board (PCB) embedding and low-temperature co-fired ceramic (LTCC) based multilayer technologies, which are insufficient for high power applications due to the limited temperature resistance and current carrying capacity. The feasibility study confirmed that the DBC embedding approach was successfully implemented by using laser technology combined with conductive gluing, solder, and silver sintering processes.<br
Keywords: Ceramic chip embedding; Cost-effective power; Electronics packaging solution; Multilayer DBC substrates; WBG packaging for industrial production

Vias in DBC Substrates for Embedded Power Modules - Bach, Hoang Linh; Yu, Zechun; Letz, Sebastian; Bayer, Christoph; Waltrich, Uwe; Schletz, Andreas; März, Martin (2018 10th International Conference on Integrated Power Electronics Systems (CIPS), 2018)
This paper encompasses an evaluation of five different approaches to produce electrical vias in DBC (Direct Bonded Copper) substrates. The investigated methods of producing vias are based on laser drilling of different via layouts in the DBC substrates. In the next step, a stencil printing, dispensing and mechanical pressing process were tested for filling the via holes. As filling material, copper, silver pastes and copper rivets were used to enable the electrical connection. Before the experiments, electrical simulations have been performed in order to analyse the optimal via layout in the DBC substrates. It could be validated that at high frequency range (1 GHz), the current density distribution improves through the increase of via pitch, via diameter and via numbers. Combined with silver paste as filling material, the electrical characteristics of produced blind-hole vias could be improved compared to the use of copper paste and copper rivets. In conclusion, potential application possibilities for vias in DBC substrate, like three-dimensional power modules, multilayer DBC stacks and chip embedding concepts are discussed.<br